2017
DOI: 10.1103/physrevd.95.064060
|View full text |Cite
|
Sign up to set email alerts
|

R -mode frequencies of rapidly and differentially rotating relativistic neutron stars

Abstract: R-modes of neutron stars could be a source of gravitational waves for ground based detectors. If the precise frequency σ is known, guided gravitational wave searches with enhanced detectability are possible. Because of its physical importance many authors have calculated the r-mode frequency. For the dominant mode, the associated gravitational wave frequency is 4/3 times the angular velocity of the star Ω, subject to various corrections of which relativistic and rotational corrections are the most important. T… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 42 publications
1
26
0
Order By: Relevance
“…This relation is independent on EOS and it is a good approximation for the slowly rotating NSs. However, according to numerical results, inclusion of relativistic corrections may increase f GW by a few tens of percent (Lockitch et al, 2003;Pons et al, 2005;Idrisy et al, 2015;Jasiulek & Chirenti, 2017). Exact value depends mostly on the object compactness C (dimensionless massradius ratio: C ≈ 0.207 M 1.4 M 10 km R , for NSs typically 0.11 C 0.31), but also on rotational frequency of the object (Lindblom et al, 1999;Idrisy et al, 2015;Jasiulek & Chirenti, 2017), including rigid versus differential rotation (Stavridis et al, 2007;Idrisy 12 Unlike in the case of the elastic deformations, what was shown in Section 2, r-modes affect equation of motion δv = α(r/R) l RωY B lm exp(iω r t), where α is dimensionless amplitude and ω r = − 2m l(l+1) ω is the angular frequency in co-rotating frame.…”
Section: Oscillationsmentioning
confidence: 99%
See 1 more Smart Citation
“…This relation is independent on EOS and it is a good approximation for the slowly rotating NSs. However, according to numerical results, inclusion of relativistic corrections may increase f GW by a few tens of percent (Lockitch et al, 2003;Pons et al, 2005;Idrisy et al, 2015;Jasiulek & Chirenti, 2017). Exact value depends mostly on the object compactness C (dimensionless massradius ratio: C ≈ 0.207 M 1.4 M 10 km R , for NSs typically 0.11 C 0.31), but also on rotational frequency of the object (Lindblom et al, 1999;Idrisy et al, 2015;Jasiulek & Chirenti, 2017), including rigid versus differential rotation (Stavridis et al, 2007;Idrisy 12 Unlike in the case of the elastic deformations, what was shown in Section 2, r-modes affect equation of motion δv = α(r/R) l RωY B lm exp(iω r t), where α is dimensionless amplitude and ω r = − 2m l(l+1) ω is the angular frequency in co-rotating frame.…”
Section: Oscillationsmentioning
confidence: 99%
“…2019)). For the more detailed review of the topic see Kokkotas & Schwenzer (2016Jasiulek & Chirenti, 2017), stiffness of the crust Levin & Ushomirsky, 2001) and EOS (Lockitch et al, 2003;Pons et al, 2005;Lattimer & Prakash, 2007;Idrisy et al, 2015). Additionally, as it was shown in Arras et al (2003), consideration of the non-linear coupling forces among internal modes leads to the result that r-mode signal from both newly born NSs and LMXB in the spin-down phase of Levin's limit cycle 13 (Levin , 1999) will be detectable by enhanced LIGO detectors out to ∼100-200 kpc.…”
Section: Oscillationsmentioning
confidence: 99%
“…The most obvious and important improvement that is needed is to go beyond the Cowling approximation. In Jasiulek & Chirenti (2017) we presented a first direct computation of the error in the r-mode frequencies due to the Cowling approximation. This was done by extrapolating our numerical results, obtained for fast rotating relativistic polytropic stars in the Cowling approximation, to f → 0 (which gives the κ 0 term in eq.…”
Section: Going Beyond the Cowling Approximationmentioning
confidence: 99%
“…A small amount of differential rotation could be present in neutron stars in LMXBs, and it might be relevant for the determination of the r-mode frequencies in stars with high compactness (Jasiulek & Chirenti 2017). More specifically, r-modes (as well as accretion) could be responsible for generating differential rotation in a neutron star, but viscosity in general and magnetic braking in particular could quickly bring the star back to uniform rotation (Rezzolla et al 2001a,b).…”
Section: Differential Rotationmentioning
confidence: 99%
See 1 more Smart Citation